Genetic investigations in pearl millet for yield components, rust and blast diseases: Genetic Investigations in Pearl Millet for rust and blast - Bharath Kumara K; B. K. Athoni; C. D. Soregaon; Kumbar , Basana (Annals of Arid Zone, 2023)
Three A1 CMS sources (ICMB 94555, ICMB 98222 and ICMB 96666) were crossed with fifteen potential restorer lines in a line × tester fashion to develop 45 hybrids. All the eighteen parents were evaluated for genetic variability parameters for eleven different quantitative traits. Moderate value of GCV and high value of PCV were observed for the trait grain yield. High estimates of heritability coupled with high genetic advance as per cent of mean was detected for the traits like plant height, panicle length, panicle girth and grain yield, revealing that these traits might be governed by additive gene effects and simple selection would lead to faster genetic enhancement of the genotypes under study. All the crosses along with their parents and checks (GHB 558, VPMH 7 and Kaveri super boss) were screened for rust and blast diseases to identify the resistant hybrids and parents, under field conditions in kharif 2021. Only one hybrid ICMA 96666 × PRLN 133 showed resistance towards both rust and blast diseases.